Contingencies and characteristics of service recovery system design: Insights from retail banking. Issue 11 (7th November 2016) - Contiero, Enrico; Ponsignon, Frederic; Smart, Philip Andrew; Vinelli, Andrea
Abstract : Purpose: The purpose of this paper is to explore the contingencies and characteristics of service recovery system (SRS) design. Design/methodology/approach: Informed by extensive case study data from two large Italian retail banks, the theory-building study builds on the seven design characteristics proposed by Smith et al. (2009). In all, 19 sub-dimensions are identified that provide a finer-grain view of the SRS at the operational level. The design characteristics and the corresponding sub-dimensions comprise the SRS design framework. These sub-dimensions are then analysed across the two cases. Specific attention is given to sub-dimensions that are contingent upon service recovery strategy. Findings: The findings suggest that the extended set of SRS sub-dimensions (providing greater specificity) contributes to identifying commonality and difference between SRS configurations. This specificity facilitates the identification of two sets of SRS design characteristics (S-type and C-type) that correspond with the SR strategy. Two propositions have been formulated with respect to this SR strategy – SRS contingency. An additional set of sub-dimensions, common to both cases, is explained by conformance to regulatory control. Originality/value: The paper provides novel theoretical insights into SRS design. The increased specificity of the SRS framework and the sets of sub-dimensions contingent on SR strategy extend the current theory. This provides opportunities for both practising managers and for future theoretical development.